Peran Mahasiswa KKN dalam Pemberdayaan Siswa MTs Sabilal Muhtadin Guna Meningkatkan Pembelajaran Bahasa Ingrris di Desa Jaya Karet - Umi Maisarah; Baharudin Nur; Nova Widya Rahmawati; Rizki Febriyana (Lembaga Pengembangan Kinerja Dosen, 2024)
Integrating academic knowledge with social devotion is the focus of MTS Sabilal Muhtadin's actual work course (KKN), particularly in the area of education. This article examines how students might use digital technology, interactive teaching strategies, and individual approaches to enhance their English language proficiency. This article's field observations show that after taking part in the KKG program, students' motivation, speaking skills, and comprehension of English-language materials all improved. But it also talks about the difficulties in putting non-educational activities into practice, such the absence of educational resources and perspectives. Empowerment through KNN activities has a huge long-term impact since students' improved English proficiency may boost their competitiveness in the labour market and give them access to a variety of global information sources. All things considered, the KNN exercise at MTS Sabilal Muhtadin demonstrates how combining science and community service may benefit both students and communities at large.